Low-residual alkali Li5FeO4 and preparation method thereof
By calcining Li5FeO4 twice and grinding nanooxides, the residual alkali value of Li5FeO4 was successfully reduced, the problem of high residual alkali value in lithium-ion batteries was solved, and the performance and safety of the battery were improved.
Patent Information
- Application Number
- CN202510097316.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-05-02
AI Technical Summary
Li5FeO4 has a high residual alkali value in lithium-ion batteries, resulting in a decrease in battery cycle stability and safety, affecting battery performance.
The first calcination treatment is performed by mixing the iron source and the lithium source, followed by mixing with the nanooxide for grinding, and finally a second calcination treatment is performed to significantly reduce the residual alkali value of Li5FeO4.
It effectively reduces the residual alkali value of Li5FeO4 and improves the overall performance and safety of lithium-ion batteries.
Smart Images

Figure CN119911973A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium-ion battery positive electrode lithium supplementing agents, and in particular to a low-residual alkali Li5FeO4 and a preparation method thereof. Background Art
[0002] Traditional lithium-ion battery positive electrode materials are prone to lithium loss when used with high-capacity negative electrode materials, resulting in battery capacity decay and reduced battery performance. In order to avoid the impact of lithium loss on battery performance, positive electrode lithium supplements are usually required.
[0003] Li5FeO4 is a commonly used positive electrode lithium supplement that can release additional lithium ions during the first charge to compensate for the lithium loss in the battery, thereby extending the battery life and improving the overall performance of the battery. Li5FeO4 has good economy, thermal stability and environmental friendliness, and has broad application prospects in improving the performance of lithium-ion batteries.
[0004] When Li5FeO4 is used as a positive electrode lithium supplement in lithium-ion batteries, the residual alkalinity value of Li5FeO4 is a key indicator. If the residual alkalinity value is high, it will cause side reactions of the electrode material in the electrolyte, reducing the cycle stability and safety of the battery. In addition, too much residual alkalinity may also react adversely with other materials in the battery to produce insoluble by-products, increase the internal resistance of the battery, and further affect the performance of the battery. Therefore, in order to achieve the effective application of Li5FeO4 in lithium-ion batteries, it is necessary to reduce its residual alkalinity value as much as possible to improve the overall performance and safety of the battery.
[0005] In the prior art, some researchers have reduced the residual alkalinity of the material by coating metal oxides on the outside of Li5FeO4 and using the metal oxides to react with the residual lithium on the surface of Li5FeO4. However, this treatment method does not significantly reduce the residual alkalinity, and the residual alkalinity still needs to be further reduced. Summary of the invention
[0006] In view of the technical problems existing in the background technology, the present application provides a low residual alkali Li5FeO4 and a preparation method thereof, aiming to solve the technical problem of high residual alkali value of Li5FeO4.
[0007] In a first aspect, the present invention provides a method for preparing low residual alkali Li5FeO4, comprising the following steps:
[0008] The iron source and the lithium source are mixed and subjected to a first calcination treatment to obtain a first calcination product;
[0009] The calcined product is mixed with nano-oxides and subjected to grinding treatment to obtain a composite product;
[0010] The composite product is subjected to a second calcination treatment to obtain low residual alkali Li5FeO4.
[0011] In the technical solution of the embodiment of the present application, by first performing a first calcination treatment on the iron source and the lithium source, and then introducing nano-oxides to mix with the calcined product and performing a grinding treatment, the particle size of the calcined product can be significantly reduced, and the nano-oxides can be attached to the surface of the calcined product; on this basis, the residual alkali on the surface of Li5FeO4 is removed by a second calcination treatment, which can significantly reduce the residual alkali value and obtain low residual alkali Li5FeO4.
[0012] In some embodiments, the first calcination treatment includes a first stage calcination and a second stage calcination performed sequentially; the first stage calcination is performed at 500-600°C for 5-10 hours; the second stage calcination is performed at 700-900°C for 20-30 hours.
[0013] In this embodiment, by performing calcination in two stages, it is possible to ensure that the reaction between the iron source and the lithium source is fully carried out, reduce the reaction residue of the lithium source, and reduce the amount of residual alkali generated.
[0014] In some embodiments, the molar ratio of the iron element in the iron source to the lithium element in the lithium source is 1:(5.08-5.12).
[0015] In this embodiment, by regulating the molar ratio of the iron element in the iron source and the lithium element in the lithium source, it is ensured that the iron element in the iron source can fully react, and the excessive amount of residual alkali caused by the introduction of too much lithium element is avoided, so that the excess residual alkali can be fully removed by nano-oxide in the subsequent process, thereby reducing the residual alkali value of the final product.
[0016] In some embodiments, the iron source includes at least one of iron oxide, ferroferric oxide, iron hydroxide, iron oxalate, iron nitrate, iron sulfate, and iron fluoride; the lithium source includes at least one of lithium oxide, lithium hydroxide, lithium carbonate, lithium nitrate, lithium sulfate, and lithium fluoride; the nano-oxide includes at least one of nano-aluminum oxide, nano-tungsten oxide, nano-niobium oxide, nano-titanium dioxide, and nano-silicon dioxide.
[0017] In this embodiment, the iron source, lithium source, and nano-oxide used are from a wide range of sources and can be selected according to actual needs, which is conducive to industrial large-scale production.
[0018] In some embodiments, the nano-oxide includes nano-tungsten oxide and / or nano-niobium oxide.
[0019] In the preferred nano-oxide of this embodiment, the metal element has a higher valence state, and the metal element can diffuse into Li5FeO4 during the second calcination treatment process, so that the valence state of the Fe element is slightly increased, thereby significantly improving the conductivity of Li5FeO4.
[0020] In some embodiments, the particle size of the nano-oxide is in the range of 10 to 500 nm.
[0021] In this embodiment, by controlling the particle size of the nano oxide to 10-500 nm, the nano oxide acts as a grinding aid, which is beneficial for controlling the particle size of the composite product during the grinding process, and further controlling the particle size of the low residual alkali Li5FeO4 obtained after the second calcination treatment of the composite product.
[0022] In some embodiments, in the composite product, the mass fraction of the nano-oxide is 1% to 5%.
[0023] In this embodiment, by controlling the mass fraction of the nano-oxide, the first calcined product can be fully ground and fully reacted with the residual alkali during the second calcination treatment, thereby obtaining Li5FeO4 with a small particle size and a low residual alkali value.
[0024] In some embodiments, the grinding treatment is performed by ball milling at a rotation speed of 100 to 600 rpm for 2 to 8 hours to obtain a composite product with a particle size range of 1 to 100 μm.
[0025] In this embodiment, by adopting ball milling to perform grinding treatment and adjusting the corresponding rotation speed and ball milling time, the nano oxide can be used as a grinding aid to fully grind the calcined product, thereby effectively reducing the particle size of the composite product.
[0026] In some embodiments, the second calcination treatment is performed by calcining at 700-1000° C. for 20-30 hours.
[0027] In this embodiment, by controlling the conditions of the second calcination treatment, the nano-oxide can be diffused into the interior of Li5FeO4 while promoting the full reaction between the nano-oxide and the residual alkali on the surface of Li5FeO4, thereby achieving a doping effect, thereby reducing the migration energy of lithium ions and further improving the capacity.
[0028] In some embodiments, before the composite product is subjected to the second calcination treatment, the composite product is subjected to an instantaneous high temperature treatment; wherein the instantaneous high temperature treatment is performed by calcining at 1200-1500° C. for 5-15 minutes.
[0029] In this embodiment, by first performing an instantaneous high temperature treatment and then performing a second calcination treatment, it is more conducive to promoting the diffusion of nano-oxide into the interior of Li5FeO4, thereby creating more defects in the interior of Li5FeO4 and significantly reducing the migration energy of lithium ions.
[0030] In the second aspect, the embodiment of the present application provides a low residual alkali Li5FeO4, which is prepared by the preparation method of the low residual alkali Li5FeO4 provided in the first aspect; the median particle size D of the low residual alkali Li5FeO4 50 The particle size is 3 to 5 μm, and the residual alkali value is less than 0.35%.
[0031] In the technical solution of the embodiment of the present application, the obtained Li5FeO4 has a small particle size and a low residual alkali value. Applying it to lithium-ion batteries is beneficial to improving the overall performance and safety of the batteries.
[0032] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0034] Figure 1 This is a flow chart for preparing low residual alkali Li5FeO4 in the examples of this application;
[0035] Figure 2 The XRD diagram of the product obtained after the first calcination treatment and the second calcination treatment in Example 1 of the present application;
[0036] Figure 3 The Fe element K-edge XANES spectra of the products obtained after the first calcination treatment and the second calcination treatment in Example 1 of the present application;
[0037] Figure 4 FT-EXAFS spectra of the products obtained after the first calcination treatment and the second calcination treatment in Example 1 of the present application;
[0038] Figure 5 This is the first charging curve of the product obtained after the first calcination treatment and the second calcination treatment in Example 1 of the present application. DETAILED DESCRIPTION
[0039] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0040] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0041] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0042] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0043] During the preparation of Li5FeO4, residual alkali is easily generated, and the presence of residual alkali will reduce the cycle stability and safety of the battery and increase the internal resistance of the battery. Conventional treatment methods are difficult to effectively reduce the amount of residual alkali on the surface, resulting in a high residual alkali value in the existing Li5FeO4, which affects the effective application of Li5FeO4 in lithium-ion batteries.
[0044] In order to solve the technical problem of high residual alkali value of Li5FeO4, the present application provides a low residual alkali Li5FeO4 and a preparation method thereof, by introducing nano-oxide and grinding it together with Li5FeO4 containing residual alkali, and then performing a second calcination treatment, thereby significantly reducing the particle size and residual alkali value of Li5FeO4.
[0045] In a first aspect, the present invention provides a method for preparing low residual alkali Li5FeO4, comprising the following steps:
[0046] The iron source and the lithium source are mixed and subjected to a first calcination treatment to obtain a first calcination product;
[0047] The calcined product is mixed with nano-oxide and subjected to grinding treatment to obtain a composite product;
[0048] The composite product is subjected to a second calcination treatment to obtain low residual alkali Li5FeO4.
[0049] Among them, you can refer to Figure 1 The content shown is that during the process of fully mixing and grinding the introduced nano oxide with the calcined product, on the one hand, the nano oxide can be used as a grinding aid to effectively reduce the particle size of the calcined product, thereby making the low residual alkali Li5FeO4 finally obtained have a smaller particle size, which is beneficial for mixing it with other components in the positive electrode active material when applied to lithium-ion batteries, and evenly distributed on the current collector, thereby improving the electrical performance of the battery. On the other hand, the nano oxide can be evenly dispersed and fully coated on the surface of the calcined product during the mixing and grinding process, and the reduction in the particle size of the calcined product is also beneficial to increase its surface area, thereby increasing the contact area between the nano oxide and the calcined product; on this basis, a second calcination treatment is performed, so that the nano oxide and the residual alkali on the surface of the calcined product can fully react with a larger contact area, thereby significantly reducing the residual alkali value of Li5FeO4.
[0050] Furthermore, in some embodiments, the first calcination treatment includes a first stage calcination and a second stage calcination performed sequentially; the first stage calcination is performed at 500-600°C for 5-10 hours; the second stage calcination is performed at 700-900°C for 20-30 hours.
[0051] In the technical solution of the embodiment of the present application, the first calcination is completed in two stages, that is, the first stage calcination is first carried out at a relatively low temperature, and then the temperature is increased to carry out the second stage calcination. The high-temperature step-by-step calcination can ensure that the reaction between the iron source and the lithium source is fully carried out, and the residual lithium source during the reaction process is reduced, thereby reducing the amount of residual alkali produced, thereby reducing the difficulty of subsequent removal of the residual alkali.
[0052] Furthermore, in some embodiments, the molar ratio of the iron element in the iron source to the lithium element in the lithium source is 1:(5.08-5.12).
[0053] In the present application, by regulating the molar ratio of the iron element in the iron source and the lithium element in the lithium source, the amount of the lithium element is only slightly higher than its theoretical amount of substance, which can ensure that the reaction is fully carried out and avoid the excessive amount of residual alkali caused by the introduction of too much lithium element, so that the excess residual alkali can be fully removed by nano oxides in the subsequent preparation of low residual alkali Li5FeO4. Specifically, the molar ratio of the iron element in the iron source and the lithium element in the lithium source can be 1:5.08, 1:5.09, 1:5.10, 1:5.11, 1:5.12 or any value in the range of 1:(5.08-5.12).
[0054] Further, in some embodiments, the iron source includes at least one of iron oxide, ferroferric oxide, iron hydroxide, iron oxalate, iron nitrate, iron sulfate, and iron fluoride; the lithium source includes at least one of lithium oxide, lithium hydroxide, lithium carbonate, lithium nitrate, lithium sulfate, and lithium fluoride; the nano-oxide includes at least one of nano-aluminum oxide, nano-tungsten oxide, nano-niobium oxide, nano-titanium dioxide, and nano-silicon dioxide.
[0055] In the technical solution of the embodiment of the present application, the iron source, lithium source, and nano-oxide used are from a wide range of sources and can be selected according to actual needs, which is conducive to industrial large-scale production.
[0056] Furthermore, in some embodiments, the nano-oxide includes nano-tungsten oxide and / or nano-niobium oxide.
[0057] In the technical solution of the embodiment of the present application, the metal element in the preferred nano-oxide has a higher valence state. The metal element can diffuse into Li5FeO4 during the second calcination treatment process, slightly increasing the valence state of the Fe element, thereby significantly improving the conductivity of Li5FeO4.
[0058] Furthermore, in some embodiments, the particle size of the nano-oxide is in the range of 10 to 500 nm.
[0059] In the technical solution of the embodiment of the present application, by controlling the particle size of the nano oxide to 10 to 500 nm, it can be used as a grinding aid to reduce the particle size of Li5FeO4 during the grinding process, and can also ensure that it is fully dispersed and attached to the surface of Li5FeO4 during the grinding process, fully react with the residual alkali on the surface of Li5FeO4 during the second calcination treatment, and diffuse the metal in the nano oxide into Li5FeO4 to achieve a doping effect. Specifically, the particle size of the nano oxide can be 10 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm or any value within the range of 10 to 500 nm.
[0060] Furthermore, in some embodiments, in the composite product, the mass fraction of the nano-oxide is preferably 1% to 5%, and more preferably 1% to 3%.
[0061] In the technical solution of the embodiment of the present application, by controlling the mass fraction of the nano-oxide, the first calcined product can be fully ground, and in the second calcination process, it can fully react with the residual alkali and be doped, thereby obtaining Li5FeO4 with a small particle size and a low residual alkali value. If the mass fraction of the nano-oxide is too low, it is difficult to achieve a good grinding aid effect, and it will also affect the subsequent reaction and doping process; if the mass fraction of the nano-oxide is too high, it will not only increase the cost of raw materials, but also cause the final Li5FeO4 to have a larger particle size, affecting its electrical properties during application.
[0062] Furthermore, in some embodiments, the grinding treatment is performed by ball milling at a rotation speed of 100 to 600 rpm for 2 to 8 hours to obtain a composite product with a particle size range of 1 to 100 μm.
[0063] In the technical solution of the embodiment of the present application, by adopting ball milling to carry out grinding treatment and regulating the corresponding rotation speed and ball milling time, the nano-oxide can be used as a grinding aid to fully grind the first calcined product, while effectively reducing the particle size of the composite product, it can also promote the nano-oxide to be fully dispersed and evenly coated on the surface of Li5FeO4, which is beneficial to fully react with the residual alkali on the surface of Li5FeO4 during the second calcination treatment, effectively reducing the residual alkali value.
[0064] Furthermore, in some embodiments, the second calcination treatment is performed at 700-1000° C. for 20-30 hours.
[0065] In the technical solution of the embodiment of the present application, by calcining the composite product at 700-1000°C, not only can the nano-oxide be promoted to fully react with the residual alkali on the surface of Li5FeO4, but the nano-oxide can also be diffused into Li5FeO4 to achieve a doping effect, thereby changing the structure of Li5FeO4 and the intrinsic ionic and electronic conductivity, reducing the migration energy of lithium ions, and applying it to lithium-ion batteries can achieve the effect of increasing capacity.
[0066] Furthermore, in some embodiments, before the composite product is subjected to the second calcination treatment, the composite product is subjected to an instantaneous high temperature treatment; the instantaneous high temperature treatment is performed by calcining at 1200-1500° C. for 5-15 min.
[0067] In the technical solution of the embodiment of the present application, by first performing an instantaneous high-temperature treatment and then performing a second calcination treatment, not only can the reaction degree of the nano-oxide and the residual alkali be improved and the residual alkali value be further reduced, but the diffusion of the nano-oxide into the interior of Li5FeO4 can also be more effectively promoted, thereby creating more defects in the interior of Li5FeO4 and significantly reducing the migration energy of lithium ions.
[0068] In the second aspect, the embodiment of the present application provides a low residual alkali Li5FeO4, which is prepared by the preparation method of the low residual alkali Li5FeO4 provided in the first aspect; the median particle size D of the low residual alkali Li5FeO4 50 The particle size is 3 to 5 μm, and the residual alkali value is less than 0.35%.
[0069] In the technical solution of the embodiment of the present application, the obtained Li5FeO4 has a small particle size and a low residual alkali value. Applying it to lithium-ion batteries is beneficial to improving the overall performance and safety of the batteries.
[0070] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.
[0071] 1. Preparation method
[0072] Example 1
[0073] This embodiment provides a method for preparing low residual alkali Li5FeO4, comprising the following steps:
[0074] S1. Fe2O3 is used as an iron source, and a mixture of Li2O and LiOH is used as a lithium source. They are weighed and placed in a mixer. The molar ratio of LiOH and Li2O is 1:2, and the molar ratio of the iron element in the iron source to the lithium element in the lithium source is 1:5.1. After stirring at a speed of 40 rpm for 5 hours until the mixture is evenly mixed, a first calcination treatment is performed under an argon atmosphere: first the temperature is raised to 550°C, and the temperature is kept for 8 hours, and then the temperature is raised to 800°C and the temperature is kept for 25 hours; a calcined product is obtained after the calcination treatment.
[0075] S2. After the calcined product is crushed, nano-niobium oxide with a particle size range of 10 to 20 nm is added so that the mass of the nano-niobium oxide accounts for 3% of the total mass of the calcined product and the product, and then ball milled at a speed of 300 rpm for 5 hours to uniformly deposit the nano-niobium oxide on the surface of the Li5FeO4 particles to obtain a composite product.
[0076] S3. The composite product is subjected to instantaneous high-temperature treatment: the composite product is kept at 1350°C for 10 minutes under an argon atmosphere; then a second calcination treatment is performed: the composite product is kept at 800°C for 25 hours under an argon atmosphere; after the calcination treatment, low residual alkali Li5FeO4 is obtained.
[0077] Example 2
[0078] This embodiment provides a method for preparing low residual alkali Li5FeO4. Compared with Example 1, the only difference is that the particle size range of nano niobium oxide used in step S2 is changed to 50-100 nm. The remaining steps are basically the same as those in Example 1 and will not be repeated here.
[0079] Example 3
[0080] This embodiment provides a method for preparing low residual alkali Li5FeO4. Compared with Example 1, the only difference is that the particle size range of nano niobium oxide used in step S2 is changed to 300-500nm. The remaining steps are basically the same as Example 1 and will not be repeated here.
[0081] Example 4
[0082] This embodiment provides a method for preparing low-residual alkali Li5FeO4. Compared with Embodiment 1, the only difference is that the mass fraction of nano-niobium oxide used in step S2 is changed to 1%. The remaining steps are basically the same as those in Embodiment 1 and will not be repeated here.
[0083] Example 5
[0084] This embodiment provides a method for preparing low residual alkali Li5FeO4. Compared with Embodiment 1, the only difference is that the mass fraction of nano niobium oxide used in step S2 is changed to 5%. The remaining steps are basically the same as those in Embodiment 1 and will not be repeated here.
[0085] Example 6
[0086] This embodiment provides a method for preparing low residual alkali Li5FeO4. Compared with Example 1, the only difference is that the nano niobium oxide used in step S2 is replaced by nano aluminum oxide of the same mass and size. The remaining steps are basically the same as those in Example 1 and will not be repeated here.
[0087] Example 7
[0088] This embodiment provides a method for preparing low residual alkali Li5FeO4. Compared with Example 1, the only difference is that the nano niobium oxide used in step S2 is replaced by nano tungsten oxide of the same mass and size. The remaining steps are basically the same as those in Example 1 and will not be repeated here.
[0089] Example 8
[0090] This embodiment provides a method for preparing low residual alkali Li5FeO4. Compared with the embodiment 1, the only difference is that the instantaneous high temperature treatment in step S3 is deleted, and only the second calcination treatment is performed on the composite product. The remaining steps are basically the same as those in the embodiment 1 and will not be repeated here.
[0091] Comparative Example 1
[0092] This comparative example provides a method for preparing low residual alkali Li5FeO4. Compared with Example 1, the only difference is that the order of adding materials and ball milling in step S2 is changed. In this comparative example, after the calcined product is crushed, it is first ball milled at a speed of 300rpm for 5h, and then nano niobium oxide with a particle size range of 10-20nm is added, and its amount is consistent with that in Example 1. The mixture of the two is placed in a mixer and stirred at a speed of 40rpm for 5h until it is evenly mixed to obtain a composite product. The remaining steps of this comparative example are basically the same as those in Example 1 and will not be repeated here.
[0093] Comparative Example 2
[0094] This comparative example provides a method for preparing low residual alkali Li5FeO4. Compared with Example 1, the only difference is that the particle size range of nano niobium oxide used in step S2 is changed to 1-2 μm. The remaining steps are basically the same as Example 1 and will not be repeated here.
[0095] Comparative Example 3
[0096] This comparative example provides a method for preparing low residual alkali Li5FeO4. Compared with Example 1, the only difference is that the particle size range of nano niobium oxide used in step S2 is changed to 2-10 μm. The remaining steps are basically the same as Example 1 and will not be repeated here.
[0097] Comparative Example 4
[0098] This comparative example provides a method for preparing low-residual alkali Li5FeO4. Compared with Example 1, the only difference is that nano-niobium oxide is not added in step S2. The remaining steps are basically the same as those in Example 1 and will not be repeated here.
[0099] Comparative Example 5
[0100] This comparative example provides a method for preparing low residual alkali Li5FeO4. Compared with Example 1, the only difference is that the conditions of the first calcination treatment in step S1 are changed to: in an oxygen atmosphere, first heat to 500°C, keep warm for 5 hours, then heat to 700°C, and keep warm for 8 hours. The remaining steps are basically the same as in Example 1 and will not be repeated here.
[0101] Comparative Example 6
[0102] This comparative example provides a method for preparing low residual alkali Li5FeO4. Compared with Example 1, the only difference is that the conditions of the second calcination treatment in step S3 are changed to: in an oxygen atmosphere, the temperature is raised to 600°C and kept warm for 5 hours. The remaining steps are basically the same as in Example 1 and will not be repeated here.
[0103] Comparative Example 7
[0104] This comparative example provides a method for preparing low residual alkali Li5FeO4. Compared with Example 1, the only difference is that the mass fraction of nano niobium oxide used in step S2 is changed to 0.1%. The remaining steps are basically the same as those in Example 1 and will not be repeated here.
[0105] Comparative Example 8
[0106] This comparative example provides a method for preparing low-residual alkali Li5FeO4. Compared with Example 1, the only difference is that the nano-niobium oxide used in step S2 is replaced by nano-zinc oxide. The remaining steps are basically the same as those in Example 1 and will not be repeated here.
[0107] 2. Test Method
[0108] 1. XRD test
[0109] The products obtained after the first calcination and the second calcination in Example 1 were tested by X-ray diffractometer. Figure 2 shown.
[0110] 2. X-ray absorption near-edge structure detection
[0111] The products obtained after the first calcination and the second calcination in Example 1 were subjected to X-ray absorption near-edge structure detection, and the following results were obtained: Figure 3 The K-edge XANES spectrum of Fe element is shown.
[0112] 3. X-ray absorption spectroscopy detection
[0113] The products obtained after the first calcination and the second calcination in Example 1 were subjected to X-ray absorption spectroscopy detection, and the following results were obtained: Figure 4 FT-EXAFS spectrum shown.
[0114] 4. Electrochemical performance test
[0115] The electrochemical performance test was carried out using a button-type semi-battery: the products obtained after the first calcination treatment and the second calcination treatment in Example 1 were respectively used as positive electrode materials, the positive electrode material, conductive carbon black and binder PVDF (polyvinylidene fluoride) were mixed into a slurry at a ratio of 8:1:1, and evenly coated on an aluminum foil to make a positive electrode sheet, a metal lithium sheet was used as a negative electrode sheet, 1 mol / L LiPF6 was used as an electrolyte, and the solvent was EC:DMC:EMC=1:1:1 (volume ratio). In a vacuum glove box, the battery case, positive and negative electrode sheets, diaphragm (PE double-layer ceramic diaphragm), spring sheet, and gasket were assembled into a button battery, and its first charging curve was measured. The results are as follows: Figure 5 shown.
[0116] The positive electrode materials prepared in Examples 2-8 and Comparative Examples 1-8 were respectively assembled into button batteries in the above manner, and their charging capacities were measured under the conditions of a voltage of 4.3 and a rate of 0.05C. The results are shown in Table 2.
[0117] 5. Particle size test
[0118] The particle sizes of the low residual alkali Li5FeO4 prepared in Examples 1-8 and Comparative Examples 1-8 were respectively detected using a laser particle size analyzer. The results are shown in Table 1.
[0119] 6. Residual alkali value test
[0120] The low residual alkali Li5FeO4 prepared in Examples 1-8 and Comparative Examples 1-8 was added to ultrapure water and the volume was fixed. Hydrochloric acid was added for titration using potentiometric titration. The titration end point was determined using a potentiometric titrator. The corresponding residual alkali value was calculated based on the amount of hydrochloric acid consumed. The results are shown in Table 2.
[0121] III. Analysis of test results of various embodiments and comparative examples
[0122] Depend on Figure 2 It can be seen that the products obtained from the first calcination treatment and the second calcination treatment in Example 1 are both Li5FeO4, and the two calcination treatments performed in Example 1 do not significantly affect the phase composition of Li5FeO4.
[0123] Depend on Figure 3-5 It can be seen that after the second calcination treatment, the Nb element in the nano-niobium oxide introduced in Example 1 diffuses into Li5FeO4 for doping. Due to the doping of the pentavalent Nb element, the valence state of the Fe element in Li5FeO4 increases slightly after the second calcination treatment, making Figure 3 The K edge shifts to the right. This will significantly improve the conductivity of Li5FeO4, making it easier for the Li element to escape, thereby significantly reducing the migration energy of lithium ions while reducing the residual alkali, which is beneficial to improving the capacity. At the same time, after doping with the Nb element, the strength of the Fe-O bond in its R space is reduced, which indicates that more defects are formed after the introduction of nano niobium oxide and the second calcination treatment, which is also beneficial to the migration of Li ions, thereby improving its specific capacity and ultimately reducing the charging platform. Therefore, in Example 1, by introducing nano niobium oxide and performing a second calcination treatment, doping can be performed while reducing the residual alkali, effectively improving its electrochemical performance.
[0124] The particle size and residual alkali value data of Li5FeO4 prepared in Examples 1-8 and Comparative Examples 1-8 are shown in Table 1 and Table 2, respectively.
[0125] Table 1 Particle size data of Li5FeO4 prepared in Examples 1-8 and Comparative Examples 1-8
[0126]
[0127] Table 2 Residual alkalinity data of Li5FeO4 prepared in Examples 1-8 and Comparative Examples 1-8 and electrochemical performance data of batteries assembled from corresponding Li5FeO4.
[0128] Residual alkali value (%) Charging capacity (mAh / g) Example 1 0.12 823.7 Example 2 0.28 798.1 Example 3 0.32 754.3 Example 4 0.35 763.1 Example 5 0.16 769.1 Example 6 0.21 745.3 Example 7 0.19 799.6 Example 8 0.27 734.1 Comparative Example 1 0.35 711.7 Comparative Example 2 0.48 737.3 Comparative Example 3 0.58 712.1 Comparative Example 4 1.03 680.1 Comparative Example 5 0.29 728.3 Comparative Example 6 0.58 721.2 Comparative Example 7 1.19 673.2 Comparative Example 8 0.98 691.1
[0129] It can be seen from Tables 1 and 2 that based on the method provided in each embodiment of the present application, by introducing nano-oxide and ball-milling it together with the first calcination product, and then combining it with a second calcination treatment, the particle size and residual alkali value of Li5FeO4 can be effectively reduced, and its electrochemical performance can be improved.
[0130] Specifically, by comparing the data of Example 1 and Comparative Example 1, it can be seen that if the nano oxide is not introduced during the ball milling process, and the nano oxide is simply mixed with the calcined product after ball milling, the particle size of the product cannot be effectively reduced, resulting in a larger particle size and a higher residual alkali value of the obtained low residual alkali Li5FeO4. By comparing the data of Examples 1 to 3 and Comparative Examples 2 to 3, it can be seen that with the increase in the particle size of the nano oxide, the size and residual alkali value of the obtained Li5FeO4 also gradually increase. By comparing the data of Example 1, Examples 4 to 5 and Comparative Examples 4 and Comparative Example 7, it can be seen that appropriately increasing the mass fraction of nano oxide within a certain range can not only reduce the particle size and residual alkali value of Li5FeO4, but also increase its charging capacity. By comparing the data of Example 1, Examples 6 to 7 and Comparative Example 8, it can be seen that the type of nano oxide will also affect the residual alkali value and electrochemical properties of the obtained Li5FeO4. The preferred nano tungsten oxide and nano niobium oxide in the embodiments of the present application are more conducive to reducing the residual alkali value of Li5FeO4 and increasing its charging capacity compared to other nano oxides. By comparing the data of Example 1, Example 8 and Comparative Examples 5 to 6, it can be seen that the present application can effectively eliminate the residual alkali on the surface of Li5FeO4 and diffuse the nano-oxide into the interior of Li5FeO4 to create more defects and reduce the energy of lithium ion escape, thereby achieving the effect of improving capacity by combining instantaneous high temperature with the second calcination treatment and controlling the temperature and atmosphere of the second calcination.
[0131] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A method for preparing low residual alkali Li5FeO4, characterized in that: The following steps are involved: The iron source and the lithium source are mixed and subjected to a first calcination treatment to obtain a first calcination product; The calcined product is mixed with nano-oxides and subjected to grinding treatment to obtain a composite product; The composite product is subjected to a second calcination treatment to obtain low residual alkali Li5FeO4.
2. The method for preparing low residual alkali Li5FeO4 according to claim 1, characterized in that: The first calcination treatment includes a first stage calcination and a second stage calcination performed sequentially; the first stage calcination is performed at 500-600°C for 5-10 hours; the second stage calcination is performed at 700-900°C for 20-30 hours.
3. The method for preparing low residual alkali Li5FeO4 according to claim 1, characterized in that: The molar ratio of the iron element in the iron source to the lithium element in the lithium source is 1:(5.08-5.12).
4. The method for preparing low residual alkali Li5FeO4 according to claim 1, characterized in that: The iron source includes at least one of iron oxide, ferroferric oxide, iron hydroxide, iron oxalate, iron nitrate, iron sulfate, and iron fluoride; the lithium source includes at least one of lithium oxide, lithium hydroxide, lithium carbonate, lithium nitrate, lithium sulfate, and lithium fluoride.
5. The method for preparing low residual alkali Li5FeO4 according to claim 1, characterized in that: The nano-oxide includes at least one of nano-aluminum oxide, nano-tungsten oxide, nano-niobium oxide, nano-titanium dioxide, and nano-silicon dioxide.
6. The method for preparing low residual alkali Li5FeO4 according to claim 1, characterized in that: The particle size of the nano oxide is in the range of 10 to 500 nm.
7. The method for preparing low residual alkali Li5FeO4 according to claim 1, characterized in that: In the composite product, the mass fraction of the nano-oxide is 1% to 5%.
8. The method for preparing low residual alkali Li5FeO4 according to claim 1, characterized in that: The grinding treatment is performed by ball milling at a rotation speed of 100 to 600 rpm for 2 to 8 hours to obtain a composite product with a particle size range of 1 to 100 μm.
9. The method for preparing low residual alkali Li5FeO4 according to claim 1, characterized in that: The second calcination treatment is performed by calcining at 700-1000° C. for 20-30 hours.
10. A low residual alkali Li5FeO4, characterized in that: Prepared by the preparation method described in any one of claims 1 to 9; the median particle size D of the low residual alkali Li5FeO4 50 The particle size is 3 to 5 μm, and the residual alkali value is less than 0.35%.
Citation Information
Cited By
A high-capacity high-stability lithium ion battery lithium supplement additive and a preparation method thereof
CN122552662A